OS DISCURSOS BÁSICOS DA SALA DE AULA. PARA UMA RETÓRICA DA INTERAÇÃO DIDÁTICA - Passeggi, Luis (Intercâmbio, 2010)
This paper presents an analysis of the verbal interaction in classroom which is composed by five basic sorts of discourses: the contents discourse, the routine discourse, the personal discourse, the representation discourse and the outside discourse. This typology, empirically suitable, must be complemented by examining the discourses’ distributions along the class period, its linguistics marks, its subtypes, its articulation and construction. By referring the results of the analyses to teacher’s formation, we suggest the inclusion of a "rethoric of a didactic interaction" in wide sense of knowledge and a practical skill of dialogical and intercational procedures including the planning aspects and the discourse composition, specially the contents discourse.